Application of Cooperative Learning Model with TPACK in Improving Learning Outcomes of Grade 7 - Anisa Meilinda Wardani; Nurul Imamah; Yanti Indah Mursyida (Universitas Teknokrat Indonesia, 2025)
This study aims to improve the learning outcomes of Grade 7 students in Mathematics by applying a cooperative learning model integrated with the Technological Pedagogical and Content Knowledge (TPACK) framework. The research was conducted at SMP Negeri 5 Jember with 32 students as participants. This classroom action research was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. The findings indicate that students' learning outcomes increased significantly after the implementation of the TPACK-assisted cooperative learning model. The percentage of students achieving minimum mastery criteria improved from 21.87% in the pre-cycle to 87.50% in the second cycle, representing a classical improvement of 65.63%. These results suggest that the integration of TPACK in cooperative learning effectively enhances students’ engagement and academic achievement in Mathematics.